Die Eigentumsverhältnisse und die Verwaltungsstruktur der oberschlesischen Industrie 1939 - 1945 [The ownership and administrative structure of Upper Silesian industry 1939 - 1945] - Sulik, Alfred (Studia Historiae Oeconomicae, 1979)
This article analyzes the changes in ownership structures and administrative organization of Upper Silesian industry during the German occupation in World War II. Following the invasion of Poland in September 1939, the highly developed industrial region of Eastern Upper Silesia was immediately incorporated into the German Reich. Due to its significant coal, iron, zinc, and energy resources, the region played a key role in the Third Reich’s war economy. The aim of this study is to examine the mechanisms of economic "reorganization" that transformed property relations and integrated Upper Silesia’s industrial potential into the German armaments industry. The study draws on extensive archival sources, including records from the Treuhandstelle Ost (Trust Office East), the Gau Chamber of Commerce for Upper Silesia, various Reich ministries, as well as contemporary German and Polish reports. Findings show that immediately after the occupation, the German authorities confiscated hundreds of industrial enterprises and placed them under temporary administration. Within months, these enterprises – particularly in mining, metallurgy, chemicals, textiles, energy, and machinery – were transferred to major German state and private conglomerates such as Reichswerke Hermann Göring, IG Farben, Preussag, Krupp, and Giesche. At the same time, a large number of small, unprofitable plants were shut down. These transfers of ownership and administrative reforms were aimed at maximizing exploitation of industrial capacity for wartime purposes and were often accompanied by coercion. By 1941, the economic reorganization was largely complete, though legal ownership disputes continued in some cases until 1944. The study demonstrates how closely economic, political, and ideological goals of the Nazi occupation were intertwined – with profound consequences for the industrial landscape of Upper Silesia.